ANALISIS PENGARUH INVESTASI, INDEKS PEMBANGUNAN MANUSIA, UPAH MINIMUM, PERTUMBUHAN EKONOMI, PENDIDIKAN TERHADAP PENGANGGURAN DI PROVINSI BANTEN TAHUN 2017-2022 - Fahriani Kurnia Putri; Yuni Prihadi Utomo (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Unemployment is a condition caused by an imbalance between the number of workforce and job opportunities. The problem of unemployment is not only experienced by developing countries, but this unemployment problem is also experienced by developed countries. Indonesia, as a member of the Association of Southeast Asian Nations and the Group of Twenty, is actively involved in promoting sustainable economic development. However, Indonesia continues to face challenges in absorbing labor within a macroeconomic framework that leads to unemployment problems. This situation threatens the welfare of its citizens, which has the potential to damage social and political stability. Therefore, it is important to conduct research that focuses on unemployment. This study aims to analyze the effect of investment, Human Development Index, Regency/City Minimum Wages, economic growth, Education in Banten Province. The study uses panel data regression, with a combination of time series data from 2017 to 2022 and cross-section data from 4 Regencies and 4 Cities in Banten Province. The results of this study indicate that the Human Development Index, economic growth, Education have an effect on unemployment because the development of Human Resources increases, economic growth, skilled labor can increase labor absorption. Meanwhile, investment and the Regency/City Minimum Wage do not affect unemployment because they only focus on capital-intensive sectors and there are still many companies that do not comply with the Regency/City Minimum Wage regulations. This study found the importance of increasing the Human Development Index, inclusive economic growth, and workforce skills as strategies in reducing unemployment in Banten Province.